Structure and Substrate Recruitment of the Human Spindle Checkpoint Kinase Bub1 - Kang, Jungseog (2008)
In mitosis, the spindle checkpoint detects a single unattached kinetochore, inhibits the anaphase-promoting complex or cyclosome (APC/C), and prevents premature sister-chromatid separation. The checkpoint kinase Bub1 contributes to checkpoint sensitivity through phosphorylating the APC/C activator, Cdc20, and inhibiting APC/C catalytically. We report here the crystal structure of the kinase domain of Bub1, revealing the requirement of an N-terminal extension for its kinase activity. Though the activation segment of Bub1 is ordered and has structural features indicative of active kinases, the C-terminal portion of this segment sterically restricts substrate access to the active site. Bub1 uses docking motifs, so-called KEN boxes, outside its kinase domain to recruit Cdc20, one of two known KEN-box receptors. The KEN boxes of Bub1 are required for the spindle checkpoint in human cells. Therefore, its unusual active-site conformation and mode of substrate recruitment suggest that Bub1 has an exquisitely tuned specificity for Cdc20.